1 . 18 × 2 × 2 + 17 =
2 . 2 × 2 × 4 × 3 =
3 . 59 + ( 48 - 46 ) × 3 =
4 . 10 × ( 2 + 7 ) =
5 . ( 37 - 24 ) × 6 =
6 . 44 ÷ (2 + 9) =
7 . 66 + ( 49 - 45 ) × 2 =
8 . 2 × 4 × 2 × 5 =
9 . ( 2 + 34 ) × 2 =
10 . ( 9 + 27 ) ÷ 9 =
11 . ( 5 + 2 ) × 2 =
12 . 6 × 3 + 10 =
13 . ( 21 ÷ 3 + 33 ) × 2 =
14 . ( 7 × 6 + 32 ) ÷ 37 =
15 . 98 - 36 - 42 =
16 . 45 ÷ 5 ÷ 3 + 37 =
17 . 41 + 17 + 4 + 19 =
18 . 4 × ( 36 ÷ 6 - 5 ) =
19 . 58 - 15 - 42 =
20 . 56 ÷ ( 55 - 41 ) =
21 . 11 + 31 + 19 + 29 =
22 . 8 + ( 69 - 63 ) × 9 =
23 . 78 ÷ (17 + 22) =
24 . 24 × 4 - ( 54 - 51 ) =
25 . ( 18 × 4 + 19 ) ÷ 13 =
26 . 2 × ( 44 + 4 ) =
27 . 67 - 38 - 5 - 18 =
28 . ( 57 + 21 ) ÷ 26 =
29 . ( 3 + 2 ) × 9 =
30 . 83 - 5 - 16 - 14 =
31 . 4 × 4 + 27 =
32 . 5 × 4 × 6 - 36 =
33 . 4 × 6 × 2 × 2 =
34 . 52 ÷ (19 + 7) =
35 . 79 + ( 45 - 44 ) × 8 =
36 . 2 × 7 × 2 × 3 =
37 . ( 89- 9) ÷ 10 =
38 . ( 24 + 66 ) ÷ 9 =
39 . 42 + 15 + 7 + 23 =
40 . 31 + ( 74 - 67 ) × 7 =
41 . 60 + ( 97 - 94 ) × 5 =
42 . 2 × 2 × 2 × 2 =
43 . 3 + 39 + 54 =
44 . 41 - 4 - 6 - 14 =
45 . 8 × 5 + 56 =
46 . 49 ÷ ( 69 - 62 ) =
47 . 22 + 19 + 20 + 30 =
48 . ( 38 + 34 ) ÷ 9 =
49 . 10 × 7 + 24 =
50 . 54 ÷ (3 + 3) =
51 . 69 - 15 - 31 - 9 =
52 . 7 + ( 22 - 2 ) × 3 =
53 . 3 × 5 + 48 =
54 . ( 58 - 53 ) × 5 =
55 . 3 × 2 × 4 × 4 =
56 . 42 ÷ 2 ÷ 3 + 40 =
57 . ( 36-
三年级四则混合运算题 来自淘豆网m.daumloan.com转载请标明出处.